Peer conformity and hedonistic lifestyle among Indonesian university students - Angelika Anggreni; Khatleen Cromley; Angeline Vanessa; Fikri Bukhori; Nurvica Sari; Rina Mirza (Universitas Ahmad Dahlan, 2026)
Peer conformity is considered a key social factor that may contribute to students’ tendencies to adopt a hedonistic lifestyle. Despite increasing concerns regarding hedonistic behaviors among university students, empirical research examining the role of peer conformity within the Indonesian higher education context remains limited. This study aimed to investigate the relationship between peer conformity and hedonistic lifestyle tendencies among university students. A quantitative correlational design was employed involving 243 undergraduate students from the Faculty of Psychology at a university in Indonesia, selected using stratified random sampling. Data were collected using Likert-scale instruments measuring peer conformity and hedonistic lifestyle tendencies. The results of Pearson correlation analysis indicated a significant positive relationship between peer conformity and hedonistic lifestyle tendencies (r = 0.571, p < 0.001). These findings suggest that higher levels of peer conformity are associated with stronger tendencies toward a hedonistic lifestyle. The study contributes to social psychological literature by emphasizing the role of peer dynamics in shaping lifestyle behaviors during emerging adulthood. Practically, the findings highlight the importance of developing educational interventions and peer influence management programs to promote healthier lifestyle choices and psychological well-being among university students.